E-learning-based speech therapy: a web application for speech training - Beijer, Lilian J; Rietveld, Toni C M; van Beers, Marijn M A; Slangen, Robert M L; van den Heuvel, Henk; de Swart, Bert J M; Geurts, Alexander C H (Telemedicine journal and e-health, 2010)
Abstract In The Netherlands, a web application for speech training, E-learning-based speech therapy (EST), has been developed for patients with dysarthria, a speech disorder resulting from acquired neurological impairments such as stroke or Parkinson's disease. In this report, the EST infrastructure and its potentials for both therapists and patients are elucidated. EST provides patients with dysarthria the opportunity to engage in intensive speech training in their own environment, in addition to undergoing the traditional face-to-face therapy. Moreover, patients with chronic dysarthria can use EST to independently maintain the quality of their speech once the face-to-face sessions with their speech therapist have been completed. This telerehabilitation application allows therapists to remotely compose speech training programs tailored to suit each individual patient. Moreover, therapists can remotely monitor and evaluate changes in the patient's speech. In addition to its value as a device for composing, monitoring, and carrying out web-based speech training, the EST system compiles a database of dysarthric speech. This database is vital for further scientific research in this area.